Pendampingan Pembentukan Ikatan Warga Ponorogo di Hong Kong (IWPH) sebagai Upaya Penguatan Jaringan Sosial dan Advokasi Bagi Pekerja Migran Indonesia - Deby Febriyan Eprilianto; Suci Megawati; Galih Wahyu Pradana; Vita Mahadhika; Dita Perwitasari; Dwi Anggorowati R; Heni Purwa Pamungkas; Bellina Yunitasari; Muhammad Arif Mahdiannur; Ali Hasbi Ramadani; Heru Arizal; Yuyun Eka Kartika Sari; Lisa Amelia Sari; Mohammad Hermy H (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesian Migrant Workers (PMI) abroad often face various social, legal, and cultural challenges that can increase their vulnerability in everyday life. One effort to minimize these vulnerabilities is through the establishment of regional community organizations as a platform for solidarity, advocacy, and cultural identity preservation. This community service activity aims to assist in the formation of the Ikatan Warga Ponorogo di Hong Kong (IWPH) — an association of PMI from Ponorogo working in Hong Kong. The methods employed include community needs assessment, facilitation of organizational meetings, formulation of organizational statutes and bylaws, and basic community-based advocacy training. The results of this activity showed high enthusiasm among PMI from Ponorogo to participate in this community as a forum for sharing information, social protection, and preserving regional cultural traditions abroad. Moreover, IWPH has begun to actively voice issues faced by PMI, such as overcharging, gender-based violence, and unclear employment contracts. The establishment of IWPH is expected to serve as a model for strengthening social networks and advocacy based on regional community groups, enhancing the bargaining power of Indonesian migrant workers abroad. This activity also reflects the contribution of higher education institutions in supporting the protection and empowerment of Indonesian migrant workers in various destination countries.